Ethics and war : an introduction - Lee, Steven (Steven P.) (Cambridge : Cambridge University Press, 2012)
'What are the ethical principles underpinning the idea of a just war and how should they be adapted to changing social and military circumstances? In this book, Steven P. Lee presents the basic principles of just war theory, showing how they evolved historically and how they are applied today in global relations. He examines the role of state sovereignty and individual human rights in the moral foundations of just war theory and discusses a wide range of topics including humanitarian intervention, preventive war, the moral status of civilians and enemy combatants, civil war and terrorism. He shows how just war theory relates to both pacifism and realism. Finally, he considers the future of war and the prospects for its obsolescence. His clear and wide-ranging discussion, richly illustrated with examples, will be invaluable for students and other readers interested in the ethical challenges posed by the changing nature of war'--
Machine generated contents note: 1. Understanding war in moral terms; 2. The just war tradition: a brief history; 3. When is it just to go to war?; 4. Sovereignty and human rights; 5. How should war be fought? Part I; 6. How should war be fought? Part II; 7. Civil wars; 8. Justice at the end of war.
Includes bibliographical references (p. 307-320) and index.
Keywords: Just war doctrine; War -- Moral and ethical aspects